2013
DOI: 10.1016/j.revsto.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Masseter function and skeletal malocclusion

Abstract: Summary The aim of this work is to review the relationship between the function of the masseter muscle and the occurrence of malocclusions. An analysis was made of the masseter muscle samples from subjects who underwent mandibular osteotomies. The size and proportion of type-II fibers (fast) decreases as facial height increases. Patients with mandibular asymmetry have more type-II fibers on the side of their deviation. The insulin-like growth factor and myostatin are expressed differently depending on the sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…After snap freezing, muscle samples were stored at -80 0 C prior to histologic and gene expression analysis. 1-2 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After snap freezing, muscle samples were stored at -80 0 C prior to histologic and gene expression analysis. 1-2 …”
Section: Methodsmentioning
confidence: 99%
“…1 Complex traits are quantitative or continuous conditions with a broad spectrum of presentations. For humans, variations in height, IQ, blood pressure and birth weight are complex quantitative traits which result from the interplay of genetic and environmental influences.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Malocclusions present a common pathological condition of masticatory system. They are characterized by an irregular contact between the maxillary and mandibular teeth that prevent the necessary effectiveness of jaw movement 10 . Malocclusion is usually defined as a consequence of orofacial system growth disorder, trauma, poor oral habits, genetic factors and disorders of masticatory forces balance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research by J. Sciote and collaborators has shown that variations in masseter muscle fiber type, gene expression in masseter muscle, and epigenetic changes that alter gene expression are associated with anterior open versus deep bites, mandibular retrognathism versus prognathism, and mandibular asymmetry. 3639 …”
Section: Genetic Variation In Muscle and Its Influence On Malocclusionmentioning
confidence: 99%